Simple bets to elicit private signals - Aurélien Baillon; Yan Xu (Theoretical Economics, 2021)
This paper introduces two simple betting mechanisms, Top-Flop and Threshold betting, to elicit unverifiable information from crowds. Agents are offered bets on the rating of an item about which they received a private signal versus that of a random item. We characterize conditions for the chosen bet to reveal the agents' private signal even if the underlying ratings are biased. We further provide micro-economic foundations of the ratings, which are endogenously determined by the actions of other agents in a game setting. Our mechanisms relax standard assumptions of the literature, such as common prior, and homogeneous and risk neutral agents.
Keywords: D8; C9; 330; Bets; private signals; Bayesian game; elicitation